Cultural Identity and Social Norms as Drivers of the Low-Carbon Transition: A Comparative Study of Poland and Germany - Henryk Wojtaszek; Dariusz Budrowski; Ireneusz Miciuła; Anna Kowalczyk; Irena Malinowska; Bartosz Błaszczak; Aneta Pawlińska; Adam Stecyk; Anna Bielawa; Sławomir Ozdyk (Energies)
This study examines the cultural and social dynamics influencing the low-carbon energy transition in Poland and Germany, highlighting the pivotal role of social norms and environmental identity in shaping public engagement with sustainable energy policies. The research employs a comparative qualitative analysis to understand how cultural underpinnings affect the adoption of sustainable behaviors and policy acceptance in distinct national contexts. Results indicate a profound disparity in environmental identity and social norms between the two countries, with Germany exhibiting a more integrated ecological consciousness and robust social norms that facilitate the adoption of sustainable practices. Conversely, Poland shows emergent behavioral changes influenced primarily by European Union policies and less entrenched ecological norms. The study concludes that effective energy transition strategies require not only technological and policy innovation but also cultural and social adaptability to ensure wide acceptance and implementation. Emphasizing the need for culturally informed policies, the findings suggest that aligning energy transition initiatives with prevailing social norms and identities significantly enhances their efficacy and public support.